The building trades exterior walls and roof construction - Meridian education Corporation (Bloomington : Meridian Education Corporation, 1992)
The student is shown an overview of associated construction trades. The occupations discussed include carpenters, brick and stone masons, glaziers and roofers
Keywords: Exterior walls -- Design and construction